From "perverts" to "fab five" : the media's changing depiction of gay men and lesbians - Streitmatter, Rodger (New York : Routledge, 2009)
From the Publisher: From'Perverts' to'Fab Five' tracks the dramatic change in how the American media have depicted gay people over the last half-century. Each chapter illuminates a particular media product that served as a milestone on the media's journey from demonizing homosexuals some fifty years ago to celebrating the gay community-or at least some sectors of the gay community-today. The media, Streitmatter argues, have not merely reflected the American publics shift to a more enlightened view of gay people, but they have been instrumental in propelling that change. The book spans the breadth of communication venues. Individual chapters focus on major news stories, entertainment television programs, and mainstream motion pictures that captured the public imagination while, at the same time, sending powerful messages about gay men and lesbians. Ideal for any reader interested in the changing depiction of gay men and lesbians in the media over time, or as required reading in media courses, From'Perverts' to'Fab Five' challenges our very understandings of the words'public' and'media' both.
Includes bibliographical references (p. [189]-216) and index
Keywords: Gay men -- United States -- Social conditions; Lesbians -- United States -- Social conditions; Gay men in mass media; Lesbians in mass media; Gays in popular culture -- United States; Mass media -- United States; United States -- Social conditions -- 1980-